A urea decorated (3, 24)-connected rht-type metal–organic framework exhibiting high gas uptake capability and catalytic activity1. Issue 25 (7th July 2015) - Wang, Xiao-Jun; Li, Jian; Li, Qiu-Yan; Li, Pei-Zhou; Lu, Han; Lao, Qianying; Ni, Rui; Shi, Yanhui; Zhao, Yanli
<x xml:space="preserve">Abstract</x> A urea decorated rht-MOF exhibited high gas uptake for CO2 and H2 and functioned as a heterogeneous catalyst for Friedel–Crafts reactions.